Postharvest application of growth regulators on Dioscorea alata (L.) and Dioscorea rotundata (Poir.) (2021)
Yam is a tuber that sees high demand and consumption in Colombia, whose post-harvest quality losses during storage have been a challenge for farmers. At the Universidad de Cordoba-Colombia, Agronomy Engineering program, between March and August of 2019, a trial was established to estimate the effect of two growth regulators on the variables: tuber weight loss (TWL), tuber sprouting (TS), starch on a dry basis (SD), and reducing sugars (RS) during storage for 120 days, with evaluations every 30 days. A completely randomized design with a 4×2 factorial arrangement plus two additional treatments with three replications was used. Four concentrations of abscisic acid (ABA) were tested: 0, 10, 15, and 20 mg L-1 in the species D. alata and D. rotundata, plus paclobutrazol (PBZ): 15 mL kg-1, for a total of 10 treatments. Each experiment unit consisted of 12 tubers that were preserved in darkness at 23°C and 53% relative humidity on average. ABA and PBZ exerted effective control over the sprouting and weight loss of the tubers during the first 90 days of storage in both species, which averaged 24.4%, i.e. approximately 488 g, favoring high starch contents, and did not influence the reducing sugar content.